ANATOMI TUMOR KAYU PADA SENGON TRUBUSAN YANG TERSERANG JAMUR Uromycladium tepperianum - , SHOFI RUKHAMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sengon (Falcataria moluccana (Miq.) Barneby & J.W. Grimes) is a fast growing species with short - harvest period, simple culture technique, high productivity, and is able to grow in all soil condition.Regeneration through coppice has several advantages, among others, the relatively more rapid growth, the volume of wood produced more and can reduce the cost of planting. But problem appears when it tends to be fragile by attack of gall rust of Uromycladium tepperianum. This disease inhibits growth, produces defect on stem reducing volume and wood quality, even leads to the death as the worst effect. This research aims to investigate the anatomy of gall rust in sengon and its wood anatomical changes representing by the arrangement, size and amount of cell. Completely randomized designed was used as research method with two main factors were the condition of gall rust and wood. Gall rust condition included three differences on size diameter which were big ( > 1.1 cm), medium ( 0.8 â 1 cm) and small (< 0.8 cm) while wood condition parameters were attacked wood and infected wood. Result was shown through anatomy of gall rust and wood cells. In gall rust anatomy, dark substrate contents and vessel elements showed an increase as the size of gall rust increased which were from 4,59% to 7,44% and 13,67% and 14,15% respectively. The decrease of kalus from small to big of gall rust was found from 81,74% to 78,40%. Furthermore there was little fiber on the gall rust because of lack of giberelin, there sklereid skin tumors as well as the wavy pattern on the composition of the callus. The decrease at percentage and size of vessel diameter on infected wood was 2,83% and 0,14 mm respectively while in healthy wood was found 7,05% and 0,24 mm as the effects of etilen hormone. The increase of parenchyma number represented through longitudinal parenchyma and ray cells was 21,86% and 22.23% respectively in infected wood while it was 7,96% and 9,54% in healthy wood as result of auxin and sitokinin, and a modification deployment parenchyma into shape ribbon in infected wood behind a small gall rust.